2010
DOI: 10.1097/ijg.0b013e3181ca7708
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Central Corneal Thickness on Intraocular Pressure Measured by Goldmann Applanation Tonometry Among Selected Ethiopian Communities

Abstract: The CCT of Ethiopians is thin and hence can result in underestimation of IOP measured by GAT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
26
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 16 publications
2
26
1
Order By: Relevance
“…Although office-based tonometry is a useful technique, it is dependent on corneal properties that often lead to measurement errors. [66][67][68][69] Furthermore, testing only involves brief measurements four times a year and the measurements do not adequately reflect diurnal and longer-term IOP variability.…”
mentioning
confidence: 99%
“…Although office-based tonometry is a useful technique, it is dependent on corneal properties that often lead to measurement errors. [66][67][68][69] Furthermore, testing only involves brief measurements four times a year and the measurements do not adequately reflect diurnal and longer-term IOP variability.…”
mentioning
confidence: 99%
“…A positive, but inconsistent association between CCT and IOP was found in South Africa [28], IOP is significantly affected by CCT in Ethiopia and Nigeria [9,29], CCT was negatively correlated with age in Cameroon [10], and there was no significant association between CCT and IOP in Nigeria [26]. Elsewhere, there was a strong correlation between CCT and IOP among the non-glaucomatous population.…”
Section: IImentioning
confidence: 99%
“…Perhaps this maximum value for children (maximum value) is just confirmation of some constatation, showed the CCT was thinner for older than for younger age. It was found of many studies led in SSA [9,10,24,25,26,27] such as elsewhere [6,32,33]. And that study showed no statistically significant difference in CCT between the age groups [23].…”
Section: IImentioning
confidence: 99%
See 2 more Smart Citations